Do annual preventive examinations lead to better mortality outcomes?. Issue 8 (August 2016) - Mayo, Russell; Downs, Michael; Fu, Cherry; Horner, David
Abstract : Evidence‐Based Answer : No. Routine periodic physical health examinations do not lead to improved cardiovascular, cancer, or total mortality outcomes (SOR: A, meta‐analyses of RCTs).